CHROMIUM SPECIATION IN ORGANIC FERTILIZERS BY SPECTROPHOTOMETRY - Arthur Felipe Burg; Graciela Marini Hiedrich; Ana Barbosa Viana; Valderi Luiz Dressler (Química Nova, 2024)
In the present study a spectrophotometric method for Cr(VI) determination in organic fertilizers, especially those from tanning industry residues, is proposed. Conditions for chromium extraction, extract clean-up and analytical characteristics of the method were established. The method is based on the complexation of Cr(VI) with 1,5-diphenylcarbazide (DPC) in acid medium (pH 2.0). A mixture of NaOH and Na2CO3 solution at 0.125 and 0.07 mol L–1 (pH 12), respectively, and heating at 90 °C for 60 min were the best conditions for chromium extraction. Florisil and activated charcoal were tested for clean-up of the extract, with activated charcoal being effective. Under the established conditions, the calibration linear range is up to 2500 μg L–1 Cr(VI), the results obtained are in agreement with the value of a certified reference material (CRM041), precision is better than 5% for five consecutive determinations of a solution at 1000 μg L–1 of Cr(VI) and the limit of quantification is 1.62 μg g–1. In can be concluded that the method is robust, accurate and precise, and can be easily applied for the determination of Cr(VI) in routine analysis, since it complies with legislation of most countries regarding the maximum allowed concentration of 2 μg g–1 of Cr(VI).